Dissociable effects of basolateral amygdala lesions on decision making biases in rats when loss or gain is emphasized - Tremblay, Melanie; Cocker, Paul J.; Hosking, Jay G.; Zeeb, Fiona D.; Rogers, Robert D.; Winstanley, Catharine A. (Cognitive, affective, & behavioral neuroscience, 2014)
Individuals switch from risk seeking to risk aversion when mathematically identical options are described in terms of loss versus gains, as exemplified in the reflection and framing effects. Determining the neurobiology underlying such cognitive biases could inform our understanding of decision making in health and disease. Although reports vary, data using human subjects have implicated the amygdala in such biases. Animal models enable more detailed investigation of neurobiological mechanisms. We therefore tested whether basolateral amygdala (BLA) lesions would affect risk preference for gains or losses in rats. Choices in both paradigms were always between options of equal expected value—a guaranteed outcome, or the 50:50 chance of double or nothing. In the loss-chasing task, most rats exhibited strong risk seeking preferences, gambling at the risk of incurring double the penalty, regardless of the size of the guaranteed loss. In the betting task, the majority of animals were equivocal in their choice, irrespective of bet size; however, a wager-sensitive subgroup progressively shifted away from the uncertain option as the bet size increased, which is reminiscent of risk aversion. BLA lesions increased preference for the smaller guaranteed loss in the loss-chasing task, without affecting choice on the betting task, which is indicative of reduced risk seeking for losses, but intact risk aversion for gains. These data support the hypothesis that the amygdala plays a more prominent role in choice biases related to losses. Given the importance of the amygdala in representing negative affect, the aversive emotional reaction to loss, rather than aberrant estimations of probability or loss magnitude, may underlie risk seeking for losses.